Controle e ressincronização de uma microrrede ilhada com validação em protótipo de escala reduzida - Alves, André Guilherme Peixoto (2018)
The growth of sensible loads in all the costumer sectors is leading the electric utilities to increase the reliability of the distribution system. One of the solutions arrived through the concept of autonomous microgrids, which possess energy distributed resources controlled to be able to operate disconnected from the main grid. This work focuses in designing and creating an autonomous reduced-scale microgrid prototype, which consists of low power converters with different control strategies and loads interconnected with each other. A special type of control is also proposed for the resynchronization process with the main grid. Experimental results are presented.